Changing dynamics of psychoneuroimmunology during the COVID-19 pandemic (2020)
The Coronavirus Disease-2019 (COVID-19) pandemic has led to a global health care crisis. Emerging research suggest an unanticipated impact of COVID-19 on mental and/or psychological health of both the general community and affected individuals. The fear of the COVID-19 epidemic and the consequent lockdown and economic crisis has led to globally increased psychological distress. The biological bases of immediate and new onset of psychiatric symptoms in individuals with COVID-19 are not yet known. COVID-19 infection may lead to activated immune-inflammatory pathways and a cytokine storm. Activated immune-inflammatory pathways, especially chronic low-grade inflammation, are associated with major psychiatric disorders in at least a subset of individuals. We propose that both the (sub)chronic inflammatory response and cytokine storm might crucially be involved in the immediate manifestation of neuropsychiatric symptoms in individuals with COVID-19 infection as well as heightened expression of psychiatric symptoms in COVID-19 infected individuals with prior psychiatric conditions. These events might expand concepts in psychoneuroimmunology, with the importance of chronic-low grade inflammation augmented by the cytokine storm hypothesis. Additionally, this might augment and refine diagnosis and prognostic management as well as treatment.